Analysis of Work Accident Potential Using the Hazard Analysis and Operability Study (HAZOP) Method in Bulk Cargo Loading and Unloading Processes - Mustika Nur Hasanah; Juwan Sade (Departemen Teknik Kelautan Universitas Hasanuddin, 2026)
The bulk cargo loading and unloading process is an important part of sea and port transportation. Bulk cargo such as fertilizers, kernels, and wheat has a high risk that can endanger workers and the environment, so identification and analysis of potential hazards is needed at every stage of operation to maintain the safety and smooth loading and unloading process. This research aims to identify potential hazards that occur, provide an assessment of the risk level, and provide solutions for actions or improvements to potential risks that can occur during the process of loading and unloading fertilizer bulk cargo at Makassar Port. This research can contribute to encouraging increased compliance of Makassar Port employees to the implementation of K3 management, which not only protects personal safety, but also supports performance improvement and this research also enriches the author's knowledge through empirical experience, addition of scientific references, and the application of concepts that have been obtained during lectures. Analysis of potential occupational safety risks in the loading and unloading of bulk fertilizer cargo activities using the Hazard and Operability Study (HAZOP) method. To analyze it, it requires a literature study, data collection in the form of observations, interviews, and questionnaires, then identifying/formulating problems with the level of hazard/risk of work accidents, then classifying the risk matrix and providing solutions for corrective actions from the potential risk of occupational accident hazards. The analysis of the highest risk level was obtained in loading and unloading operations at the port and in the warehouse area which then became a reference for designing appropriate corrective action solutions so that the level of occupational safety risks at the Port of Makassar could be reduced, thereby creating a safer, more efficient, and productive work environment for all parties involved in bulk fertilizer cargo loading and unloading activities. The results obtained are how much potential danger is obtained, an assessment of likelihood, consequence, and severity in order to determine the level of low, medium, high, and extreme risk and provide the best solution in taking more targeted preventive measures.